Association Between Physical Activity, Sleep Quality and Handgrip Strength in Medical Student (Department of Physical Education, Sport, Health and Recreation, 2020)
This study was conducted to determine the association between physical activity and sleep quality with handgrip muscles strength of medical students at Universitas Pembangunan Nasional â€œVeteranâ€ Jakarta. This study was an analytical observational with cross sectional design. The participants were 75 male students aged 18-22 years old. Random sampling was used for this study. Measurement of physical activity was carried out using the Global Physical Activity Questionnaire (GPAQ) and sleep quality using the Pitsburgh Sleep Quality Index (PSQI) questionnaire. The strength of handgrip muscle was measured using Camry Handgrip Dynamometer. Result showed there was a significant association between physical activity with handgrip strength with significance value of p =0,000 (p <0,05) and sleep quality with p = 0,003 (p <0,05) using 95% CI. Multivariate test showed physical activity had more dominant association with handgrip strength with an OR score of 4,608 . Based on the result, it can be concluded student with good sleep quality and higher level of physical activity tend to have stronger handgrip muscle with physical activity as dominant factor.